Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil - Fernández, Fernando; Delabie, Jacques Hubert Charles; Nascimento, Ivan Cardoso Do (Zootaxa, 2009)
Diaphoromyrma sofiae, new genus and new species, is a Myrmicinae ant described from workers from the State of Bahia, Brazil. This taxon is characterized by the following traits: Antenna 9-segmented with 2-segmented club, trapezoidal promesonotum in dorsal view, propodeal spiracles situated on the propodeal edges, and the fourth abdominal sternite with a pair of rounded recurved anterolateral extensions which curve up onto the dorsal surface of the segment. Apparently this ant is close to the genera Allomerus and Diplomorium in the Solenopsidini, but its tribal attribution remains difficult because of the inadequate resolution of the phylogenetic relationships within the Myrmicinae.